Clinical indications for computed tomographic colonography: European Society of Gastrointestinal Endoscopy (ESGE) and European Society of Gastrointestinal and Abdominal Radiology (ESGAR) Guideline - Spada, Cristiano; Stoker, Jaap; Alarcon, Onofre; Barbaro, Federico; Bellini, Davide; Bretthauer, Michael; De Haan, Margriet C.; Dumonceau, Jean-Marc; Ferlitsch, Monika; Halligan, Steve; Helbren, Emma; Hellstrom, Mikael; Kuipers, Ernst J.; Lefere, Philippe; Mang, Thomas; Neri, Emanuele; Petruzziello, Lucio; Plumb, Andrew; Regge, Daniele; Taylor, Stuart A.; Hassan, Cesare; Laghi, Andrea (Endoscopy, 2014)
This is an official guideline of the European Society of Gastrointestinal Endoscopy (ESGE) and the European Society of Gastrointestinal and Abdominal Radiology (ESGAR). It addresses the clinical indications for the use of computed tomographic colonography (CTC). A targeted literature search was performed to evaluate the evidence supporting the use of CTC. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was adopted to define the strength of recommendations and the quality of evidence.Main recommendations1 ESGE/ESGAR recommend computed tomographic colonography (CTC) as the radiological examination of choice for the diagnosis of colorectal neoplasia. ESGE/ESGAR do not recommend barium enema in this setting (strong recommendation, high quality evidence).2 ESGE/ESGAR recommend CTC, preferably the same or next day, if colonoscopy is incomplete. Delay of CTC should be considered following endoscopic resection. In the case of obstructing colorectal cancer, preoperative contrast-enhanced CTC may also allow location or staging of malignant lesions (strong recommendation, moderate quality evidence). 3 When endoscopy is contraindicated or not possible, ESGE/ESGAR recommend CTC as an acceptable and equally sensitive alternative for patients with symptoms suggestive of colorectal cancer (strong recommendation, high quality evidence).4 ESGE/ESGAR recommend referral for endoscopic polypectomy in patients with at least one polyp ≥ 6 mm in diameter detected at CTC. CTC surveillance may be clinically considered if patients do not undergo polypectomy (strong recommendation, moderate quality evidence).5 ESGE/ESGAR do not recommend CTC as a primary test for population screening or in individuals with a positive first-degree family history of colorectal cancer (CRC). However, it may be proposed as a CRC screening test on an individual basis providing the screenee is adequately informed about test characteristics, benefits, and risks (weak recommendation, moderate quality evidence).